Amyloidosis of the gastrointestinal tract and the liver: clinical context, diagnosis and management. Issue 10 (October 2016) - Syed, Umer; Ching Companioni, Rafael A.; Alkhawam, Hassan; Walfish, Aron
Abstract : Amyloidosis is a group of disorders that can manifest in virtually any organ system in the body and is thought to be secondary to misfolding of extracellular proteins with subsequent deposition in tissues. The precursor protein that is produced in excess defines the specific amyloid type. This requires histopathological confirmation using Congo red dye with its characteristic demonstration of green birefringence under cross-polarized light. Gastrointestinal (GI) manifestations are common and the degree of organ involvement dictates the symptoms that a patient will experience. The small intestine usually has the most amyloid deposition within the GI tract. Patients generally have nonspecific findings such as abdominal pain, nausea, diarrhea, and dysphagia that can often delay the proper diagnosis. Liver involvement is seen in a majority of patients, although symptoms typically are not appreciated unless there is significant hepatic amyloid deposition. Pancreatic involvement is usually from local amyloid deposition that can lead to type 2 diabetes mellitus. In addition, patients may undergo either endoscopic or radiological evaluation; however, these findings are usually nonspecific. Management of GI amyloidosis primarily aims to treat the underlying amyloid type with supportive measures to alleviate specific GI symptoms. Liver transplant is found to have positive outcomes, especially in patients with specific variants of hereditary amyloidosis.